The Effect of Economic Growth and Wage on Employment Opportunities at Samarinda City - Satria, Wisnu; Mubarak, Muhammad Syahrul (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this study was to determine and analyze the effect of economic growth and minimum wages on employment opportunities in Samarinda City, East Kalimantan from 2004 to 2015. This type of research is quantitative descriptive and by taking data sources of literature studies. The analytical method used in this study is the Ordinary Least Square (OLS) analysis method. Based on the data analyzed in this study there are some conclusions as follows: Economic Growth has a significant effect on Job Opportunities in the city of Samarinda and the Minimum Wage has a positive and significant effect on Job Opportunities in the city of Samarinda.